Super-wear-resistant sand-sand-resistant self-cleaning photovoltaic module coating and preparation method thereof

By using fluorosiliconized modified polyacrylic resin coatings prepared on photovoltaic modules using nanodiamond and nanotin oxide antimony, the wind and sand wear problem of photovoltaic modules in the desert Gobi area is solved, and ultra-wear resistance and self-cleaning performance is achieved, and the performance of ultra-wear resistance and self-cleaning is extended. The service life is maintained and the power generation efficiency is maintained.

CN119264760AActive Publication Date: 2025-01-07GUANGZHOU XINYI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411541813.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Photovoltaic modules are susceptible to wind and sand in the desert Gobi area of ​​the northwest region, resulting in physical wear and power attenuation, affecting service life and power generation.

Method used

Ultra-wear-resistant and wind-resistant self-cleaning photovoltaic module coatings prepared from nanodiamond, nanotin oxide antimony, fluorosilicate modified polyacrylic resin and other components are used to form excellent hydrophobic and self-cleaning through plasma hydroxylation and surface hydrophobic treatment. Clean and wear-resistant coating.

Benefits of technology

The coating has excellent hydrophobic and oleophobic properties, which can naturally remove sand and dust and soil, reduce manual maintenance costs, and has ultra-high wear resistance, maintaining the cleanliness and power generation performance of the photovoltaic panel surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264760A_ABST
    Figure CN119264760A_ABST
Patent Text Reader

Abstract

The invention discloses a super wear-resistant sand-sand-resistant self-cleaning photovoltaic module coating and a preparation method thereof, and the super wear-resistant sand-sand-resistant self-cleaning photovoltaic module coating is prepared by mixing and reacting the following components in parts by weight: 18-22 parts of nano diamond, 0.5-1.5 parts of nano tin antimony oxide, 2.5-3 parts of 1H, 1H-perfluoro-1-dodecanol, 0.5-1.5 parts of sodium hydroxide, 0.5-1.5 parts of sodium hydroxide, 0.5-1.5 parts of sodium hydroxide, 0.5-1.5 parts of sodium hydroxide, 0.5- The invention relates to an acrylic resin, which is prepared from the following raw materials in parts by weight: 32 to 36 parts of octamethacrylate polyhedral oligomeric silsesquioxane, 20 to 30 parts of dicyclopentyl acrylate, 10 to 16 parts of isobornyl acrylate, 20 to 25 parts of (tricyclic [3.3.1. 1.13, 7] deca-1-yloxy) methyl methacrylate, 14 to 18 parts of 1, 6-di (acryloyloxy)-2, 2, 3, 3, 4, 4, 5, 5-octafluorohexane, 16 to 22 parts of acrylic acid 1H, 1H, 2H, 2H-tridecafluoro n-octyl ester, 40 to 50 parts of methyl methacrylate and 34 to 40 parts of hydroxyethyl methacrylate. 2.5 to 3 parts of an initiator, and 3.5 to 4.1 parts of 2-hydroxy-2-methyl-1-phenyl-1-acetone. The coating disclosed by the invention is simple in production process and low in cost, and has stable self-cleaning and wear-resisting properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and specifically relates to a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic component coating and a preparation method thereof. Background Art

[0002] As a new type of clean energy, photovoltaic power generation has many advantages over traditional power generation, such as environmental protection, pollution-free, and noise-free. It is a sustainable new energy source that my country has vigorously developed in recent years. Under the active promotion of the "dual carbon" goals, my country's photovoltaic industry has achieved leapfrog development in recent years. In the first quarter of 2024, the cumulative grid-connected capacity of distributed photovoltaics has climbed to 280 million kilowatts, fully demonstrating its wide application and important position in my country's photovoltaic power generation field. my country's northwest region has abundant sunshine, especially in Qinghai, Gansu, Xinjiang and other places, with an average annual radiation of 1600kWh / m 2 The above, at the same time, the Northwest region is vast and sparsely populated, with a large number of unused deserts and Gobi, which is very suitable for the construction of photovoltaic power generation projects. However, in the desert Gobi areas of northwest my country, photovoltaic panels are extremely vulnerable to wind and sand. Sandstorms can cause a 100% loss in the output of photovoltaic arrays, and even local coverage of dust or sand can lead to serious production cuts. The physical wear caused by wind and sand can affect the packaging structure of photovoltaic modules, causing excessive power attenuation or accelerated aging, which in turn affects the service life of the modules and the power generation of the power station. Therefore, it is particularly important to develop a self-cleaning photovoltaic panel coating that is super wear-resistant and wind-resistant. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a super wear-resistant, wind-resistant and self-cleaning photovoltaic module coating. The coating of the present invention has a simple production process, low cost, and stable self-cleaning and wear-resistant properties.

[0004] The technical solution adopted by the present invention is:

[0005] A super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating is prepared by a mixed reaction of the following components in parts by weight: 18 to 22 parts of nano-diamond, 0.5 to 1.5 parts of nano-antimony tin oxide, 2.5 to 3 parts of 1H,1H-perfluoro-1-dodecanol, 32 to 36 parts of octamethylacrylate-based cage-shaped silsesquioxane, 20 to 30 parts of dicyclopentyl acrylate, 10 to 16 parts of isobornyl acrylate, (tricyclo[3.3.1.13,7]decyl -1-yloxy) methyl methacrylate 20-25 parts, 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane 14-18 parts, acrylic acid 1H,1H,2H,2H-tridecafluorooctyl ester 16-22 parts, methyl methacrylate 40-50 parts, hydroxyethyl methacrylate 34-40 parts, initiator 2.5-3 parts, 2-hydroxy-2-methyl-1-phenyl-1-propanone 3.5-4.1 parts. The initiator can be selected from any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate in the azo initiator.

[0006] A method for preparing a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating comprises the following steps:

[0007] S1, mixing 18-22 parts of nano-diamond and 0.5-1.5 parts of nano-antimony tin oxide to form a nano-filler, and performing plasma hydroxylation treatment on the mixed nano-filler;

[0008] S2, performing surface hydrophobic treatment on the nanofiller obtained in step S1;

[0009] S3, 32-36 parts of octamethacrylate cage-shaped silsesquioxane, 20-30 parts of dicyclopentyl acrylate, 10-16 parts of isobornyl acrylate, 20-25 parts of (tricyclo[3.3.1.13,7]dec-1-yloxy)methyl methacrylate, 14-18 parts of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 16-22 parts of 1H,1H,2H,2H-tridecafluorooctyl acrylate, 40-50 parts of methyl methacrylate, 34-40 parts of hydroxyethyl methacrylate are mixed, and then a proper amount of organic solvent is added and stirred until fully dissolved, and 2.5-3 parts of initiator is slowly added at temperature T1, and the reaction is complete to obtain a fluorosiliconized modified polyacrylic acid resin body;

[0010] S4, add the hydrophobic filler prepared in step S2 to the fluorosilicone modified polyacrylic resin body obtained in step S3, disperse evenly, add 3.5 to 4.1 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, stir for a period of time, and obtain a super wear-resistant, wind-resistant, self-cleaning photovoltaic module coating. If the viscosity of the fluorosilicone modified polyacrylic resin body is too high, add an appropriate amount of organic solvent (the same as the organic solvent in step S3) to dilute it until the fluorosilicone modified polyacrylic resin does not hang on the wall.

[0011] Octamethacrylate-based cage-shaped silsesquioxane is a rigid silicon-based molecule that mainly acts as a strength enhancer and crosslinker in the coating. The silicon element in it also has a certain hydrophobic effect. Isobornyl acrylate mainly promotes the leveling of the coating and improves the construction performance.

[0012] The plasma hydroxylation treatment is a process of introducing hydroxyl groups on the surface of a material through plasma treatment.

[0013] Furthermore, the plasma hydroxylation treatment in the present invention comprises the following steps: placing the nanofiller in a plasma cleaning machine, using oxygen and hydrogen peroxide as working gases to treat the nanomaterial to obtain the nanofiller with surface hydroxylation treatment.

[0014] The surface hydrophobic treatment refers to converting the original hydrophilic material surface into a hydrophobic surface by chemical means, making it water-resistant or oil-resistant, thereby achieving the purpose of anti-fouling and water-resistant. Common surface hydrophobic treatment methods include chemical fluorination treatment, chemical siliconization treatment and mechanical processing.

[0015] Furthermore, the surface hydrophobic treatment in the present invention is to fluorinate the nanomaterial, comprising the following steps: placing the surface hydroxylated nanofiller prepared in step S1 and 2.5 to 3 parts of 1H,1H-perfluoro-1-dodecanol at both ends of the chemical vapor deposition reactor, sealing the reactor and evacuating the reactor, continuously introducing an inert gas from the end where the 1H,1H-perfluoro-1-dodecanol is placed, and then sealing the reactor again, and then heating the end where the 1H,1H-perfluoro-1-dodecanol is placed to a temperature T 2 1H,1H-perfluoro-1-dodecanol is fully vaporized to obtain a hydrophobic nanofiller. The introduction of fluorine element will reduce the surface free energy of the coating to a certain extent and improve the hydrophobic and oleophobic properties. If the amount of 1H,1H-perfluoro-1-dodecanol added is too much, it will lead to the supersaturation of fluorine-containing substances on the surface of the nanoparticles. On the one hand, too much fluorine element will affect its dispersibility in the solvent and compatibility with the resin. On the other hand, the stacking of long chains will cause the secondary particle size of the particles to become larger, affecting the transmittance of the coating. Therefore, in order to ensure the transmittance of the coating, the amount of 1H,1H-perfluoro-1-dodecanol added should not be too much.

[0016] Preferably, the organic solvent in step S3 and step S4 is any one of butyl acetate solvent, ethyl acetate and acetone.

[0017] Preferably, T 2 Greater than 224° C. The purpose of heating is to vaporize 1H,1H-perfluoro-1-dodecanol and attach it to the nanofiller.

[0018] Preferably, T 1 The temperature is 60-80°C. Heating is to accelerate the polymerization reaction rate, and too high a temperature will cause excessive evaporation of the solvent.

[0019] Preferably, the initiator in step S3 is any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate.

[0020] Preferably, the inert gas is nitrogen.

[0021] The coating formed by the coating provided by the present invention has the following beneficial effects:

[0022] 1. The coating of the present invention has excellent hydrophobic and oleophobic properties. The coating is mainly composed of fluorinated polyacrylate. The prepared coating has excellent surface properties and can repel most liquids including water and oil. After being coated on the surface of the photovoltaic panel, it can prevent water stains and oil stains from adhering to the surface and keep the surface clean.

[0023] 2. It has excellent self-cleaning performance. When solid pollutants such as sand, dust, and dirt adhere to the surface, they can be easily removed from the surface by natural rainfall or wind, reducing the cost of manual cleaning and maintenance;

[0024] 3. It has the performance of resistance to wind and sand adhesion. The antistatic coating added to the paint can reduce the adhesion of sand and dust to a certain extent, so that the coating surface remains clean for a long time;

[0025] 4. It has super high wear resistance and can resist the wear of the coating surface caused by sand and gravel in a dusty environment as well as other external stress damage. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A comparison curve of transmittance in the visible light region between the photovoltaic panel glass coated with the ultra-wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating prepared in Example 1 of the present invention and the untreated photovoltaic panel glass.

[0027] Figure 2 A graph showing the weight loss rate variation during the wear resistance test (Taber) of the ultra-wear-resistant, wind-resistant, self-cleaning photovoltaic module protective coating prepared in Example 1 of the present invention.

[0028] Figure 3 A graph showing the variation of transmittance, water contact angle and sliding angle in the wear resistance test (steel wool) of the ultra-wear-resistant, wind-resistant and self-cleaning photovoltaic module protective paint coating prepared in Example 1 of the present invention.

[0029] Figure 4 A comparative bar graph of the sample quality of the ultra-wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating prepared in Example 1 of the present invention before and after the wind-resistant test.

[0030] Figure 5 A comparison curve of power generation efficiency of a photovoltaic panel coated with the ultra-wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating prepared in Example 1 of the present invention and an untreated photovoltaic panel before and after being placed in an outdoor environment for a long time. DETAILED DESCRIPTION

[0031] The specific implementation of the present invention is described in detail below in conjunction with specific implementation examples, but the present invention is not limited to the given examples.

[0032] Unless otherwise specified, all component amounts in the present invention are parts by weight.

[0033] Example 1

[0034] The specific preparation method of the ultra-wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module protective coating provided by the present invention is as follows:

[0035] (1) 20 g of nano-diamond and 1 g of nano-antimony tin oxide were mixed into a nano-filler (a blended powder of nano-diamond and nano-ATO) and subjected to plasma hydroxylation treatment. Specifically, the blended powder of nano-diamond and nano-ATO was treated in a plasma cleaning machine (NE-PEO2) with oxygen and hydrogen peroxide as working gases for about 1 hour to obtain a nano-filler with a surface hydroxylation treatment;

[0036] (2) The nanofiller finally obtained in step (1) is subjected to a hydrophobic treatment. Specifically, the hydroxylated nanofiller prepared in step (1) and 3 g of 1H,1H-perfluoro-1-dodecanol are placed at both ends of a chemical vapor deposition dish, respectively. The deposition dish is sealed and evacuated, and nitrogen is continuously introduced from the end where the 1H,1H-perfluoro-1-dodecanol is placed, and then the deposition dish is sealed again, and then the end where the 1H,1H-perfluoro-1-dodecanol is placed is heated to T. 2 After 230°C, the temperature was maintained for 2 hours to fully vaporize 1H,1H-perfluoro-1-dodecanol, and finally the heating was stopped. After the system returned to room temperature, a hydrophobic nanofiller was obtained.

[0037] (3) 35 g of octamethacrylate cage-shaped silsesquioxane, 25 g of dicyclopentyl acrylate, 14 g of isobornyl acrylate, 23 g of (tricyclo[3.3.1.13,7]dec-1-yloxy)methyl methacrylate, 16 g of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 20 g of 1H,1H,2H,2H-tridecafluorooctyl acrylate, 45 g of methyl methacrylate, and 38 g of hydroxyethyl methacrylate were weighed into a flask, and then 500 g of butyl acetate solvent was added and stirred for 30 minutes until fully dissolved, and then placed in a flask. 1 In an 80℃ oil bath, wait until the system temperature reaches T 1 After 80℃, add 2.7g of initiator azobisisobutyronitrile dropwise while stirring. After the initiator is added dropwise, continue to maintain T 1 The polymerization reaction was carried out at 80°C for 4 hours to obtain a fluorosilicon modified polyacrylic acid resin main body;

[0038] (4) After further diluting the fluorosilicone modified polyacrylic resin body prepared in step (3) with 500 g of butyl acetate solvent, the hydrophobic filler prepared in step (2) is added thereto, and after ultrasonic dispersion for 30 minutes, 3.9 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone is added and stirred at room temperature for 1 hour to obtain an ultra-wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating;

[0039] After the glass substrate used for photovoltaic panels is rinsed alternately with anhydrous ethanol and deionized water twice, the super wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating is sprayed onto the surface of the photovoltaic glass panel. The glass panel is kept horizontal during the spraying process. After spraying, it is placed in a UV curing machine and the UV light is adjusted to a wavelength of 325nm. After curing for 15 minutes, the super wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating is obtained on the surface of the photovoltaic panel.

[0040] Example 2

[0041] The difference between this embodiment and embodiment 1 is that the addition amount of each component is: nano diamond 18g, nano antimony tin oxide 1.5g, 1H,1H-perfluoro-1-dodecanol 2.5g, T 1 At 60°C, T 2 The temperature is 224°C, and the others are the same as in Example 1.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that the addition amount of each component is: 22g of nano-diamond, 0.5g of nano-antimony tin oxide, 2.8g of 1H,1H-perfluoro-1-dodecanol, 1 The temperature is 70°C, and the others are the same as in Example 1.

[0044] Example 4

[0045] The difference between this embodiment and embodiment 1 is that the addition amount of each component is: 20g of dicyclopentyl acrylate, 10g of isobornyl acrylate, 20g of (tricyclo[3.3.1.13,7]dec-1-yloxy)methyl methacrylate, and the rest is the same as embodiment 1.

[0046] Example 5

[0047] The difference between this embodiment and embodiment 1 is that the addition amount of each component is: 30g of dicyclopentyl acrylate, 16g of isobornyl acrylate, 25g of (tricyclo[3.3.1.13,7]dec-1-yloxy)methyl methacrylate, and the rest is the same as embodiment 1.

[0048] Example 6

[0049] The difference between this embodiment and embodiment 1 is that the addition amount of each component is: 32 g of octamethacrylate cage-shaped silsesquioxane, and the rest is the same as embodiment 1.

[0050] Example 7

[0051] The difference between this embodiment and embodiment 1 is that the addition amount of each component is: 36 g of octamethacrylate cage-shaped silsesquioxane, and the rest is the same as embodiment 1.

[0052] Example 8

[0053] The difference between this embodiment and the embodiment is that the addition amount of each component is: 14g of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 16g of 1H,1H,2H,2H-tridecafluorooctyl acrylate, and 40g of methyl methacrylate, and the rest is the same as in embodiment 1.

[0054] Example 9

[0055] The difference between this embodiment and the embodiment is that the addition amount of each component is: 18g of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 22g of 1H,1H,2H,2H-tridecafluorooctyl acrylate, and 50g of methyl methacrylate, and the rest is the same as in embodiment 1.

[0056] Example 10

[0057] The difference between this embodiment and the embodiment is that the addition amount of each component is: 34g of hydroxyethyl methacrylate, 2.5g of azobisisobutyronitrile, 3.5g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the rest is the same as embodiment 1.

[0058] Embodiment 11

[0059] The difference between this embodiment and the embodiment is that the addition amount of each component is: 40g of hydroxyethyl methacrylate, 3g of azobisisobutyronitrile, 4.1g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the rest is the same as embodiment 1.

[0060] The coating prepared in the embodiment of the present invention was tested for performance as follows:

[0061] Visible light transmittance measurement: The transmittance of the samples (coated glass and untreated glass) to visible light was tested using an Agilent Cary 5000 UV-visible-near infrared spectrophotometer. The size of the test sample was 7.5 cm × 2.5 cm, and a glass slide of the same size was selected as a control sample during the test. The transmittance of air was set as the baseline for the test. The test wavelength range was 300 nm to 800 nm.

[0062] Contact angle measurement: The contact angle of water droplets / oil droplets (if not otherwise specified, the oils used in the test here are all gasoline, i.e., a mixture of aliphatic hydrocarbons and cycloalkanes) on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For the measurement of the contact angle in a non-moving state, a water droplet / oil droplet (about 10 microliters) was first added to the sample surface by a motor-controlled syringe. When the droplet is stable, a side image is taken with a camera, and the software is used for fitting calculation to obtain the static contact angle value of the water droplet / oil droplet on the coating surface.

[0063] Coating surface hardness test: The coating surface hardness is tested by pencil hardness test method, and the test is carried out according to ASTMD3363 standard. During the test, the sample to be tested is placed on a horizontal plane, and the pencil (hardness ranges from 9B-9H) is firmly placed on the coating surface at a 45° angle (pointing opposite to the tester), and it is pushed away from the tester by a quarter of an inch at a time. When testing, the hardest pencil (9H) is used for testing first, and then the hardness is gradually reduced according to the hardness scale until the pencil does not scratch the coating. At this time, the scale corresponding to the pencil is defined as the pencil hardness of the coating.

[0064] Wear resistance test: Test method (1) Taber wear tester was used to test the wear resistance of the coating according to ASTM standard test (D4060 standard). During the test, a 250g load grinding wheel ( Industries Cs-10) is used as the wear medium. First, the coating is sprayed onto a specific annular glass substrate, and then fixed to the sample stage of the Taber wear tester. A wear wheel is lowered on each side to closely adhere to the surface of the test sample. When the test starts, the sample stage will rotate with the tested sample. Here, one rotation of the sample is defined as a test cycle. When obvious wear marks appear on the coating surface, the test is defined as the end, the number of wear cycles is recorded, and the wear resistance is measured by calculating the change in the weight loss rate of the sample.

[0065] The calculation formula of weight loss rate is as follows:

[0066]

[0067] Test method (2) uses a steel wool reciprocating wear test, which is conducted on a multifunctional friction tester. In the steel wool wear test, the friction contact head is covered by a steel wool, the contact area is about 0.785 cm2, the load weight is 250 g, the conversion pressure is about 31.2 kPa, and one reciprocating movement of the contact head is defined as one wear cycle. After a specific number of wear cycles, the transmittance and hydrophobic and oleophobic properties of the coating are tested. When one of the following conditions occurs: (1) obvious scratches appear on the coating surface; (2) the transmittance is less than 90%; or (3) the water contact angle is less than 100° / the sliding angle is greater than 30°, the test is stopped and the number of wear cycles is recorded to measure the wear resistance of the coating.

[0068] Coating adhesion test: The adhesion of the coating was tested according to ASTM D3359. All test samples were cross-cut at 1 mm intervals with a QHF grid cutter, and then 3MTM 600 tape was firmly pasted on the grid area, and then a 2 kg weight was placed on the tape pasting area and slid and pressed to make the tape fully contact the test area. After 90 seconds of rest, the tape was quickly pulled apart in the vertical direction (90°), and the same area was tested twice, and then the remaining part of the coating on the substrate was observed to evaluate the adhesion of the coating. According to the standard, when the coating falls off about 0%, its adhesion is 5B grade; when the coating falls off less than 5%, the adhesion is 4B grade; when the coating falls off less than 15%, the adhesion is 3B grade; when the coating falls off less than 35%, the adhesion is 2B grade; when the coating falls off less than 65%, the adhesion is 1B grade; when the coating falls off more than 65%, the adhesion is 0B grade.

[0069] Coating wind and sand resistance performance test: The wind and sand resistance performance of the coating is tested in a sand and dust test chamber, using natural red sand as the material to simulate wind and sand, and using coated glass slides and uncoated glass slides as test samples. The samples are weighed in advance before the test. During the test, the samples are placed in the test chamber of the sand and dust test chamber at a specific inclination angle, the door is closed to keep it airtight, and then the wind and sand environment is simulated from bottom to top based on constant blowing. After the test, the mass of the sample is weighed, and the difference between the mass of the sample and the mass of the sample before the test is the mass of sand attached to the surface of the sample, which is used to measure the wind and sand resistance performance of the coating.

[0070] Self-cleaning performance of the coating: The self-cleaning performance of the coating adopts the test method in most current scientific research literature. First, a certain amount of red sand is evenly sprinkled on the surface of the sample to be tested. Then, given a certain inclination angle of the surface, an appropriate amount of water droplets are added to the upper edge of the sample to simulate rainfall under natural conditions. Then, the wetting state of the water droplets on the coating surface and the cleaning ability of the red sand on the sample surface are observed to measure the self-cleaning performance of the coating.

[0071] Comparative test of photovoltaic cell power generation efficiency: During the power generation efficiency test, commercial unpackaged photovoltaic silicon wafers were selected as test photovoltaic cells, and the surface was covered with a glass substrate sprayed with a coating and an untreated glass substrate to compare the effect of the test coating on the power generation efficiency of the battery module. The current density-voltage curve was tested by the Taitaishi PROVA200A solar cell analyzer. Both samples were simply rinsed with water before the test. The solar light source during the test was provided by the Yiguangke SOLARBEAM-06-3A sunlight simulator, simulating the irradiation intensity of AM 1.5 sunlight of about 100mWcm-2.

[0072] The coating performance tests prepared in each embodiment are shown in the following table:

[0073]

[0074] From the above test data, it can be seen that the contact angle of water droplets on the coating surface of the coating of the present invention is above 100°, indicating that the coating has excellent hydrophobic properties; the contact angle of oil droplets on the coating surface is basically above 80°, indicating that the coating has excellent oleophobic properties and excellent self-cleaning properties. Under such conditions, the adhesion of some oil pollutants and water stains on the coating surface is very low, which can avoid their adhesion on the surface and keep the surface of the photovoltaic panel clean. The weight loss rate of the Taber wear test for 8000 cycles is less than 4%, and the number of steel ball wear cycles exceeds 11000 cycles. The coating has excellent wear resistance.

[0075] Figure 1This is a comparison curve of the transmittance of photovoltaic panel glass coated with super wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating and untreated photovoltaic panel glass in the visible light region. The visible light region, that is, light in the wavelength range of 400-800 nanometers, is the main energy source for photovoltaic power generation. There is almost no difference in the transmittance of coated glass and untreated glass in the visible light region, both of which can be maintained at a level of about 92% ± 0.2%. The effect of the coating on the transmittance of photovoltaic panel glass is almost negligible, which also shows that it will not affect the original power generation efficiency of the photovoltaic panel.

[0076] Figure 2 This is a graph showing the weight loss rate change during the wear test of the ultra-wear-resistant, wind-resistant, self-cleaning photovoltaic module protective coating. As can be seen from the figure, during the Taber wear test, as the number of wear cycles increases, the quality of the coating gradually decreases. In the first 6,000 wear cycles, the coating quality decreases slowly, indicating that the coating has good wear resistance; as the test continues, the coating weight loss rate gradually accelerates, which may be due to the rough wear of the originally smooth surface of the coating, resulting in an increase in its contact area with the grinding wheel, which will cause more mass loss, but with the effect of nano-diamond filler, the strength of the coating is improved. Even if the wear reaches 10,000 cycles, the weight loss rate of the coating can still be maintained at a low level (2.11%), reflecting the excellent wear resistance of the coating.

[0077] Figure 3 This is a graph showing the change in transmittance, water contact angle and sliding angle of the wear test of the ultra-wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating. As can be seen from the figure, during the steel wool wear test, as the number of wear cycles increases, even when the wear cycle reaches 15,000 times, the transmittance of the coating only decreases slightly, the contact angle of the water droplet on the coating surface decreases from 117.45° to 103.62°, and the sliding angle increases from 16.53° to 23.77°, reflecting the excellent wear resistance of the coating. This is due to the fact that the alicyclic structure in dicyclopentyl acrylate and (tricyclo[3.3.1.13,7]dec-1-yloxy)methyl methacrylate will enhance the structural strength of the coating. At the same time, the octamethacrylate-based cage-shaped silsesquioxane in the coating is a rigid silicon-based molecular substance, which can improve the cross-linking degree inside the coating, further improve the structural strength and wear resistance of the coating, and at the same time, the silicon element in it also has a certain hydrophobic effect, enhancing the hydrophobic properties of the coating.

[0078] Figure 4This is a comparative bar graph of the sample quality of the ultra-wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating before and after the wind-resistant test. After the test, a large amount of red sand adhered to the surface of the uncoated glass sample, while the mass of the red sand adhered to the surface of the coated glass sample was much lower than that of the uncoated glass sample. This is to a certain extent due to the addition of ATO in the nanofiller. The excellent conductivity of ATO reduces the resistance of the coating surface, reduces the electrostatic force between it and the sand and dust, and avoids the adhesion of sand and dust on the surface.

[0079] Figure 5 The comparison curve of the power generation efficiency of the photovoltaic panel coated with the ultra-wear-resistant, wind-resistant and self-cleaning photovoltaic module protective coating and the untreated photovoltaic panel before and after being placed in an outdoor environment for a long time. From the comparison curve, it can be seen that at the beginning of the test, the open circuit voltage and short circuit current of the two are almost equal, which shows that the coating will not have a great impact on the original performance of the photovoltaic panel and can maintain the original power generation efficiency of the photovoltaic panel. After 90 days of outdoor placement, the power generation efficiency of the untreated photovoltaic panel has dropped significantly, which is mainly because the accumulation of pollutants on the surface of the photovoltaic panel affects the light intake and reduces the power generation level of the photovoltaic panel; while the power generation efficiency of the photovoltaic panel coated with the coating has only slightly decreased even after 90 days, which is mainly due to the excellent self-cleaning performance of the coating, which can keep the surface of the photovoltaic panel clean in the outdoor environment and maintain a high power generation level.

[0080] The present invention has been described in detail above in conjunction with specific embodiments. However, the present invention is not limited to the above description. Various changes made within the knowledge of those skilled in the art without departing from the concept of the present invention still fall within the protection scope of the present invention.

Claims

1. A super wear-resistant, wind-resistant and self-cleaning photovoltaic module coating, characterized in that: The invention is prepared by mixing and reacting the following components in parts by weight: 18 to 22 parts of nano-diamond, 0.5 to 1.5 parts of nano-antimony tin oxide, 2.5 to 3 parts of 1H,1H-perfluoro-1-dodecanol, 32 to 36 parts of octamethylacrylate-based cage-shaped silsesquioxane, 20 to 30 parts of dicyclopentyl acrylate, 10 to 16 parts of isobornyl acrylate, (tricyclo[3.3.1.13,7]dec-1-yloxy)methyl 20-25 parts of methyl acrylate, 14-18 parts of 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 16-22 parts of 1H,1H,2H,2H-tridecafluorooctyl acrylate, 40-50 parts of methyl methacrylate, 34-40 parts of hydroxyethyl methacrylate, 2.5-3 parts of initiator, and 3.5-4.1 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone.

2. The ultra-wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating according to claim 1, characterized in that: The initiator is any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate.

3. A method for preparing a super wear-resistant, wind-resistant and self-cleaning photovoltaic module coating, characterized in that: It includes the following steps: S1, mixing 18-22 parts of nano-diamond and 0.5-1.5 parts of nano-antimony tin oxide to form a nano-filler, and performing a plasma hydroxylation treatment on the mixed nano-filler; S2, performing surface hydrophobic treatment on the nanofiller obtained in step S1; S3, 32-36 parts of octamethacrylate cage-shaped silsesquioxane, 20-30 parts of dicyclopentyl acrylate, 10-16 parts of isobornyl acrylate, 20-25 parts of (tricyclo[3.3.1.13,7]dec-1-yloxy)methyl methacrylate, 14-18 parts of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 16-22 parts of 1H,1H,2H,2H-tridecafluorooctyl acrylate, 40-50 parts of methyl methacrylate, 34-40 parts of hydroxyethyl methacrylate are mixed, and then a proper amount of organic solvent is added and stirred until fully dissolved, and 2.5-3 parts of initiator is slowly added at temperature T1, and the reaction is complete to obtain a fluorosiliconized modified polyacrylic acid resin body; S4. Add the hydrophobic filler prepared in step S2 to the fluorosilicone modified polyacrylic resin body prepared in step S3, disperse evenly, add 3.5 to 4.1 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, stir for a period of time, and obtain a super wear-resistant, wind-resistant, and self-cleaning photovoltaic module coating.

4. The method for preparing a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating according to claim 2, characterized in that: The plasma hydroxylation treatment comprises the following steps: placing the nanofiller in a plasma cleaning machine, using oxygen and hydrogen peroxide as working gases to treat the nanomaterial, and obtaining the nanofiller with surface hydroxylation treatment.

5. The method for preparing a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating according to claim 2, characterized in that: The surface hydrophobic treatment is to fluorinate the nanomaterial, comprising the following steps: placing the surface hydroxylated nanofiller prepared in step S1 and 2.5 to 3 parts of 1H,1H-perfluoro-1-dodecanol at both ends of a chemical vapor deposition reactor, sealing the reactor and evacuating the reactor, continuously introducing an inert gas from the end where the 1H,1H-perfluoro-1-dodecanol is placed, and then sealing the reactor again, and then heating the end where the 1H,1H-perfluoro-1-dodecanol is placed to a temperature T2 to fully vaporize the 1H,1H-perfluoro-1-dodecanol, thereby obtaining the hydrophobic nanofiller.

6. The method for preparing a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating according to claim 3, characterized in that: The organic solvent in step S3 and step S4 is any one of butyl acetate solvent, ethyl acetate and acetone.

7. The method for preparing a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating according to claim 5, characterized in that: T2 is greater than 224°C.

8. The method for preparing a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating according to claim 3, characterized in that: T1 is 60~80℃.

9. The method for preparing a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating according to claim 3, characterized in that: The initiator in step S3 is any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate.

10. The method for preparing a super wear-resistant, wind-sand-resistant, self-cleaning photovoltaic module coating according to claim 5, characterized in that: The inert gas is nitrogen.

Citation Information

Patent Citations

  • Fluorine silicon acrylate copolymer, preparation process thereof and application thereof

    CN102351983A

  • Electronic protective coating composition with low dielectric constant and multifunction

    CN108948939A

  • High hardness wear-resistant fingerprint-proof nano coating for PC material and preparation method of high hardness wear-resistant fingerprint-proof nano coating

    CN110760256A

  • Anti-fouling coatings

    US20200115583A1

  • Radiation curable compositions with Anti-stain properties

    WO2018058505A1